Izabela Kępka, Kazania ks. Aleksandra Jełowickiego. Językowe konceptualizacje świata wartości, Wydawnictwo Uniwersytetu Gdańskiego, Gdańsk 2023, ss. 170 - Kowalewska-Dąbrowska, Jolanta (Idiolekty, 2026)
Bez